Sinonasal Findings on Paranasal Computed Tomography in Patients Presenting with Facial Pain - Raad, Nasim; Ghorbani, Jahangir; Karimi-Galougahi, Mahboobeh; Yarmohammadi, Javad (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Facial pain is one of the common complaints in otolaryngology. Patients often self-diagnose facial pain as "sinusitis". The sinonasal source of facial pain and headache could be one of the possible etiologies, which needs to be confirmed by nasal endoscopy or CT scan. Aim: This study aimed to detect the frequency of variations and pathological findings in the sinonasal region of patients presenting with facial pain and sinonasal symptoms by PNS CT imaging. Methods: This descriptive study was conducted in a tertiary referral hospital where consecutive patients presenting to the otorhinolaryngology clinic with facial pain and at least one of the sinonasal symptoms, including nasal obstruction, nasal congestion, rhinorrhea, reduction or loss of smell, and postnasal discharge, were included. For evaluation of facial pain, a paranasal sinus CT scan in coronal view was performed and analyzed by an otolaryngologist. Results: A total of 64 patients including 27 males (42%) and 37 females (57.8%) were included. The average age was 35.5±10.5. Most patients experienced bilateral facial pain (78.1%.). The most common location of pain was the forehead (76.6%). Fifteen patients (23.4%) had acute pain (<12 weeks) while 49 (76.6%) experienced chronic pain (>12 weeks). Cold weather was the most common triggering factor in 29 patients (45.3%). The most common sinonasal symptom was posterior nasal discharge (in 42 patients, 65.6%). A minority of patients, 8 (12.5%), had evidence of rhinosinusitis (acute or chronic). Ethmoid sinus was the most frequently involved sinus (9.3%), and sphenoid and frontal sinuses were the least commonly involved. 2 patients (3.1%) had unilateral complete opacification of the maxillary sinus. Conclusion: Sinusitis was not the most common cause of facial pain in the present study, even in the presence of sinonasal symptoms. The definitive diagnosis of facial pain warrants confirmation by complementary imaging before starting therapy.